IDO1 modulates pain sensitivity and comorbid anxiety in chronic migraine through microglial activation and synaptic pruning - Hu, Jiao; Ji, Wen-Juan; Liu, Gui-Yu; Su, Xiao-Hong; Zhu, Jun-Ming; Hong, Yu; Xiong, Yi-Fan; Zhao, Yun-Yan; Li, Wei-Peng; Xie, Wei (Journal of Neuroinflammation, 2025)
Chronic migraine is a prevalent and potentially debilitating neurological disorder that is often comorbid with mental health conditions (such as anxiety and depression), but the underlying mechanisms linking these conditions remain poorly understood. Indoleamine 2,3-dioxygenase 1 (IDO1) has been implicated in inflammatory processes, including neuroinflammation and pain. However, its role as a link between neuroinflammation and pain sensitization in chronic migraine is not well defined.